Strategi Peningkatan Inklusi Keuangan Syariah Melalui Platform Digital di Kalangan Pendidik Perempuan SMK Kabupaten Pati - Winarno Suryo Edi Subroto; Yayat Sujatna (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze strategies for improving Islamic financial inclusion through the utilization of digital platforms among female teachers at Vocational High Schools (SMK) in Pati Regency. This research employs a descriptive qualitative approach supported by simple quantitative data (mixed method), involving 90 respondents obtained through interviews, questionnaires, and documentation. The results indicate that the level of Islamic financial literacy is still dominated by the moderate category (47.8%), followed by the low category (27.8%) and the high category (24.4%). Meanwhile, 64.4% of respondents have utilized digital platforms, although 35.6% have not used them optimally. These findings suggest that digital platforms play a strategic role in enhancing Islamic financial inclusion, although their utilization is not yet evenly distributed. Therefore, integrated strategies are required, including strengthening digital-based Islamic financial literacy, practical training in the use of digital financial services, integration of financial literacy into Vocational High Schools (SMK) learning, collaboration with Islamic financial institutions and fintech, and strengthening digital literacy. Thus, the utilization of digital platforms can serve as an effective solution to improve Islamic financial literacy and inclusion sustainably while reinforcing the role of teachers as literacy agents within educational and community environments.